Β-Caryophyllene attenuates dextran sulfate sodium-induced colitis in mice via modulation of gene expression associated mainly with colon inflammation. (2015) - Cho, Jae Young; Kim, Hwa Yeon; Kim, Sung-Kyu; Park, Jung Han Yoon; Lee, Hong Jin; Chun, Hyang Sook
Abstract: We examined the modulatory activity of β-caryophyllene (CA) and gene expression in colitic colon tissues in a dextran sulfate sodium (DSS)-induced colitis model. Experimental colitis was induced by exposing male BALB/c mice to 5% DSS in drinking water for 7 days. CA (30 or 300 mg/kg) was administered orally once a day together with DSS. CA administration attenuated the increases in the disease activity index, colon weight/length ratio, inflammation score, and myeloperoxidase activity in DSS-treated mice. Microarray analysis showed that CA administration regulated the expression in colon tissue of inflammation-related genes including those for cytokines and chemokines (Ccl2, Ccl7, Ccl11, Ifitm3, IL-1β, IL-28, Tnfrsf1b, Tnfrsf12a); acute-phase proteins (S100a8, Saa3, Hp); adhesion molecules (Cd14, Cd55, Cd68, Mmp3, Mmp10, Sema6b, Sema7a, Anax13); and signal regulatory proteins induced by DSS. CA significantly suppressed NF-κB activity, which mediates the expression of a different set of genes. These results suggest that CA attenuates DSS-induced colitis, possibly by modulating the expression of genes associated mainly with colon inflammation through inhibition of DSS-induced NF-κB activity.